2008
DOI: 10.1007/s10340-008-0209-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the entomopathogenic nematodes Steinernema feltiae, S. weiseri and Heterorhabditis bacteriophora for the biological control of the sugar beet weevil Bothynoderes punctiventris (Coleoptera: Curculionidae)

Abstract: Potential of the entomopathogenic nematodes Steinernema feltiae, S. weiseri and Heterorhabditis bacteriophora for the biological control of the sugar beet weevil Bothynoderes punctiventris (Coleoptera: Curculionidae) Alper SusurlukAbstract The sugar beet weevil, Bothynoderes punctiventris Germ. (Coleoptera: Curculionidae), is one of the most damaging pests of sugar beets in Turkey and has been traditionally controlled by application of large amounts of insecticides. The current study used laboratory microcosms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…Laboratory studies by Akalach and Wright (1995), in Morocco indicated that S. carpocapsae and S. feltiae were effective against the sugar beet weevil Conorhynchus mendicus. Susurluk (2008) obtained encouraging results with S. feltiae and H. bacteriophora against the sugar beet weevil Bothynoderes punctiventris at different temperatures and at different depths in the soil. Laboratory results showed that the most virulent and fastest nematode against larvae of C. vittata was S. feltiae.…”
Section: Discussionmentioning
confidence: 59%
“…Laboratory studies by Akalach and Wright (1995), in Morocco indicated that S. carpocapsae and S. feltiae were effective against the sugar beet weevil Conorhynchus mendicus. Susurluk (2008) obtained encouraging results with S. feltiae and H. bacteriophora against the sugar beet weevil Bothynoderes punctiventris at different temperatures and at different depths in the soil. Laboratory results showed that the most virulent and fastest nematode against larvae of C. vittata was S. feltiae.…”
Section: Discussionmentioning
confidence: 59%
“…SL0708, greatest infectivity is presented at 20 °C, diverging from results found by Morton and Garcia-del-Pino (2009) for some species of heterorhabditidae, where 25 °C was the optimum temperature or 30 °C for Heterorhabditis georgiana (Shapiro-Ilan et al, 2009). The inconsistency in results regarding temperature for different species of the Heterorhabditis genus, shows that a single temperature cannot be assigned to the genre and that the infectivity of nematode species may also depend on the size of the larva, the depth of the host in the substrate and search behaviour of the IJs (Boff et al, 2001;Susurluk, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is recognised that temperature is an important factor in the life cycle of entomopathogenic nematodes (Griffin, 1993). Varying temperatures have effects on the viability of the IJs and their ability to reproduce, these effects are observed mainly in extreme temperatures (0 and 40 °C), which are lethal (Rohde et al, 2010;Susurluk, 2008;Morton and Garcia-del-Pino, 2009). As observed in Heterorhabditis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural and mechanical control measures shall involve spatial isolation and good organisation of the production. Biological control could be effectuated by the use of the nematodes Steinernema and Heterorhabditis (together with symbiotic bacteria Xenorhabdus and photorhabdus) for the suppression of the weevil population (Trdan et al 2006;Susurluk 2008;Hassan 2010). However, the commercial use of products based on the aforementioned organisms has not been reported.…”
Section: Discussionmentioning
confidence: 99%